Particle Physics at the Tercentenary of Mikhail Lomonosov : Proceedings of the Fifteenth Lomonosov Conference on Elementary Particle Physics. - Studenikin, A. I. (World Scientific Pub. Co., 2012)
This volume is devoted to a wide variety of investigations, both in theory and experiment, of particle physics such as electroweak theory, fundamental symmetries, tests of the Standard Model and beyond, neutrino and astroparticle physics, heavy quark physics, non-perturbative QCD, quantum gravity effects, and present and future accelerator physics.